Whole‐genome sequencing of north African honey bee Apis mellifera intermissa to assess its beneficial traits. Issue 3 (23rd March 2018) - Haddad, Nizar Jamal; Adjlane, Noureddine; Saini, Deepti; Menon, Athul; Krishnamurthy, Venkatesh; Jonklaas, Devan; Tomkins, J. Paul; Loucif‐Ayad, Wahida; Horth, Lisa
Abstract: Apis mellifera intermissa is the native honey bee subspecies of Algeria, and approximates a position among bee races between tropical African and European breeds. This bee is very aggressive, nervous, and produces many broods with many queen cells. It is prone to swarming and exhibits defensive behavior and an abundant use of propolis. In the present study, pure line samples of A. m. intermissa collected from Blida (Algeria; 36°31′N, 2°58′E) with preferable Varroa resistance confirmed their through hygienic cleaning behavior and high temperature adaptation, were selected as a reference sample for full‐genome sequencing. Array comparative genomic hybridization (aCGH) was also performed on the same samples to validate genomic variations. These analyses will be an important source of information for the honey bee research community worldwide. The 240‐Mb genome was annotated with 26 355 transcripts and analyzed. Analysis of 133 pathways indicated an abundance of pathways related to metabolic processes, the biosynthesis of secondary metabolites, and biodegradation of xenobiotics . In addition to simple sequence repeat markers, variant analysis for beneficial trait genes, transposons, and phylogeny was performed. The mitochondrial genome and genes involved in immunity and chemoreception were identified and compared with those from other sequenced insect models. The indels obtained by sequencing were validated by aCGH. The genome sequence, annotation, and analysis of A. m. intermissa provides new understanding of the function of bee genes, and comparison with the genome of other A. mellifera subspecies promises to yield insights into the evolution of the adaptations to high temperature and resistance to Varroa parasite infestation.